The cat and the city - Bradley, Nick (Atlantic Books, 2021)
"In Tokyo- one of the world's largest megacities- a stray cat is making her way through the back alleys. With each detour, she brushes up against the seemingly disparate lives of the city-dwellers, connecting them in unexpected and, at times, magical ways. But the city is changing, and as it does, it pushes her to the margins where she chances upon a series of apparant strangers- from a homeless man squatting in an abandoned hotel, to a shut-in hermit afraid to leave his house, to a convenience store worker searching for love. As the cat circles through the sprawling metropolis, she draws these intersecting lives ever closer, enmeshing them forever." -- Back cover.